Therapeutic potential of bioconstituents in the prevention and treatment of rheumatoid arthritis - Morris, Srishti; Srivastava, Yashashvi; Kartikey Kumar; Jakhmola, Vikash (Journal of Applied Pharmaceutical Research, 2025)
Background: Rheumatoid arthritis (RA), a joint disease characterized by inflammation and an autoimmune response, affects approximately 1% of the global population. The disruption of immunological tolerance causes the immune system to attack self-molecules, resulting in autoimmune disease. RA is characterized by synovial swelling, accompanied by morning stiffness and joint soreness. Methodology: Herbal pharmacotherapy is now a meaningful focus in the treatment of rheumatoid arthritis. Medicinal plants contain strong active components like flavonoids, alkaloids, stilbenoids, tannins, and sesquiterpene lactones. Their anti-inflammatory and antioxidant qualities make them a potential treatment option for RA. Results and Discussion: Standard medication aims to prevent further deterioration of the affected joint. This treatment includes several antirheumatic medications, such as methotrexate, biological agents, cytotoxic drugs, immunosuppressants, and NSAIDs. Urinary and respiratory tract infections have been reported in patients treated with certolizumab pegol. Several concerns regarding anti-rheumatoid medication arise during a woman's pregnancy. Therefore, rheumatoid arthritis is now being effectively treated with herbal pharmacotherapy. Conclusion: RA is a chronic autoimmune disorder that primarily affects joints through persistent inflammation. Conventional treatment regimens for RA can lead to the occurrence of adverse effects, such as urinary and respiratory tract infections. Given these challenges, herbal pharmacotherapy is emerging as a safer and more sustainable approach. This review highlights a variety of phytochemicals with anti-inflammatory and antiarthritic properties, including flavonoids, alkaloids, stilbenoids, tannins, and sesquiterpene lactones. It underscores the need for further research to elucidate their mechanisms of action, assess their long-term safety and clinical utility, and compare their efficacy.